Pengembangan Media Pembelajaran dengan Bantuan Aplikasi Mtestm Kemampuan Mendengar A1 - Adinda Putri Nazli; Risnovita Sari (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
The purpose of this research is to create learning media with the help of MtestM application about German language students' knowledge of listening skill A1 topic "Kennenlernen (sich vorstellen)". This research was conducted at the Language Laboratory of the Faculty of Languages and Arts, State University of Medan. This research uses Richey and Klein's model which consists of three stages, namely (1) research, (2) development, (3) evaluation. The data of this research are words, texts, sentences about "Kennenlernen" from the book Netzwerk Deutsch als Fremdsprache A1 Kursbuch by Stefanie Dengler, Paul Rusch, Helen Schmitz and Tanja Sieber pages 8-17. This interactive quiz is interesting and varied. The results of this study are German learning media and interactive quizzes for mastering the A1 listening skill 'Introducing oneself' with the help of MtestM.